Making Poor Haitians Count : Poverty in Rural and Urban Haiti Based on the First Household Survey for Haiti - Verner, Dorte (The World Bank, 2008)
This paper analyzes poverty in Haiti based on the first Living Conditions Survey of 7,186 households covering the whole country and representative at the regional level. Using a USD1 a day extreme poverty line, the analysis reveals that 49 percent of Haitian households live in absolute poverty. Twenty, 56, and 58 percent of households in metropolitan, urban, and rural areas, respectively, are poor. At the regional level, poverty is especially extensive in the northeastern and northwestern regions. Access to assets such as education and infrastructure services is highly unequal and strongly correlated with poverty. Moreover, children in indigent households attain less education than children in nonpoor households. Controlling for individual and household characteristics, location, and region, living in a rural area does not by itself affect the probability of being poor. But in rural areas female headed households are more likely to experience poverty than male headed households. Domestic migration and education are both key factors that reduce the likelihood of falling into poverty. Employment is essential to improve livelihoods and both the farm and nonfarm sector play a key role